1995
DOI: 10.1139/o95-043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoreception at the cellular level: the detection, interpretation, and diversity of responses to mechanical signals

Abstract: Cells from diverse tissues detect mechanical load signals by similar mechanisms but respond differently. The diversity of responses reflects the genotype of the cell and the mechanical demands of the resident tissue. We hypothesize that cells maintain a basal equilibrium stress state that is a function of the number and quality of focal adhesions, the polymerization state of the cytoskeleton, and the amount of extrinsic, applied mechanical deformation. A load stimulus detected by a mechano-electrochemical sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
220
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(223 citation statements)
references
References 112 publications
3
220
0
Order By: Relevance
“…In cultured human osteoblasts, ERK-1/2 blockade prevented shear-induced proliferation and matrix synthesis (43). Tenocytes appear to share elements of a load-sensing mechanism similar to osteoblasts and osteocytes; stretch-activated potassium and calcium channels, internal calcium release, interstitial ATP release, and gap junction signaling all play a role in the proliferative response to membrane deformation, substrate deformation, or fluid shear (43)(44)(45)(46)(47). In elongated tenocytes, proliferation and collagen synthesis in response to ex vivo loading of chicken flexor tendon could be blocked by a gap junction inhibitor (48).…”
Section: Discussionmentioning
confidence: 99%
“…In cultured human osteoblasts, ERK-1/2 blockade prevented shear-induced proliferation and matrix synthesis (43). Tenocytes appear to share elements of a load-sensing mechanism similar to osteoblasts and osteocytes; stretch-activated potassium and calcium channels, internal calcium release, interstitial ATP release, and gap junction signaling all play a role in the proliferative response to membrane deformation, substrate deformation, or fluid shear (43)(44)(45)(46)(47). In elongated tenocytes, proliferation and collagen synthesis in response to ex vivo loading of chicken flexor tendon could be blocked by a gap junction inhibitor (48).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that mechanical stimuli regulate various cellular functions and that the mechano-sensing system including ion channel receptors, soluble cytokines, the cytoskeleton or intracellular signaling pathways are likely to be involved in the signaling of and response to mechanical stresses in mammalian cells [2][3][4]. The regulatory role of mechanical force is believed to be critical in the remodeling of the skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanotransduction in bone must include the biochemical coupling which transduces a local mechanical signal into a biochemical signal [2]. Recent observations suggest the presence of a mechanotransducer that resides in the cell membrane of the osteoblastlike cells [15].…”
Section: Introductionmentioning
confidence: 99%